Ratio of Elephant Grass and Concentrate Containing Seaweed on Dry Matter, Organic Matter, and Crude Protein Digestibility (In Vitro) - Putri, Saskia Ramdhiani; Hidayat, Rahmat; Hidayat, Ujang; Rosani, Urip (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The limited availability of conventional feed has encouraged the development of alternative feed sources, such as the use of seaweed in rations. This study aimed to determine the effect of forage-to-concentrate ratios containing seaweed on in vitro digestibility. A Completely Randomized Design (CRD) was used with four treatments and five replications. The treatment rations consisted of RG1 = 80% Elephant Grass + 20% Concentrate, RG2 = 60% Elephant Grass + 40% Concentrate, RG3 = 40% Elephant Grass + 60% Concentrate, and RG4 = 20% Elephant Grass + 80% Concentrate. The observed parameters included dry matter digestibility, organic matter digestibility, and crude protein digestibility. Data were analyzed using analysis of variance (ANOVA) with SPSS software, followed by Duncan’s test to determine differences between treatments. The results showed that the treatments had a highly significant effect (P<0.01) on dry matter and organic matter digestibility, and a significant effect (P<0.05) on crude protein digestibility. The dry matter digestibility values were RG1 (46.63%), RG2 (49.81%), RG3 (52.58%), and RG4 (56.60%). The organic matter digestibility values were RG1 (52.90%), RG2 (55.88%), RG3 (57.81%), and RG4 (60.94%). The crude protein digestibility values were RG1 (66.26%), RG2 (70.96%), RG3 (70.20%), and RG4 (70.25%). The best forage-to-concentrate ratio containing seaweed based on digestibility values was RG4 (20:80%).